THE EFFECT OF ACTIVE LEISURE USE ON QUALITY OF LIFE IN YOUNG ADULTS - Kaplan, Mehmet; Kerkez, Müjde (Inonu University, 2024)
The aim of this study is to evaluate the effect of active leisure use on the quality of life of young adults. The study data were collected from associate degree students studying at a university between October and November 2022. The sample size of the study was 366 students. The study data were collected using a form that included sociodemographic characteristics, the Leisure Attitudes Scale and the SF-12 Quality of Life Scale. Pearson correlation analysis and Tukey test for multiple comparisons were used to evaluate the data. It was observed that the mean score of the emotional sub-dimension of the Leisure Attitude Scale was statistically higher in students who stated that their weekly leisure was sufficient. A strong relationship was found between the age of the students and the mean score of the mental component. The mean mental component scores of students who reported having enough free time per week were better than the others (p<0.05). In this study, it was determined that students' attitudes towards leisure activities were low. © 2024, Inonu University. All rights reserved.
Genç Yetişkinlerde Aktif Boş Zaman Kullanımının Yaşam Kalitesine Etkisi
Keywords: Leisure; Quality of life; Young adults